Syntactic structure and psychological law of proximity - Kiklewicz, Aleksander (Papers in Linguistics, 2023)
The subject of the article is a special type of non-accommodative relationship of syntactic components, defined as a correlative relationship: it occurs between collaterally subordinated syntactic actants that are located in the immediate closeness – in a linear contact order. The correlative relationship is based on the sentence structuring in terms of the linear order of components, and the psychological law of proximity plays a decisive role in its formation. Correlative groups are additionally conditioned by such factors as lexical identity of components, high frequency of reproduction, regularity, i.e. correspondence to the phrase patterns. Some correlative groups are compact – they have a common position and a common syntactic function, and they have partly also a phraseological character. One of the widespread types of correlative groups is realized within the bounds of coordinate relationship, e.g. ma <blizny na brzuchu> i <otarcia na łapach>.